2017
DOI: 10.1016/j.jaci.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Addendum guidelines for the prevention of peanut allergy in the United States: Report of the National Institute of Allergy and Infectious Diseases–sponsored expert panel

Abstract: Background Food allergy is an important public health problem because it affects children and adults, it may be severe and even life-threatening, and it may be increasing in prevalence. Beginning in 2008, the National Institute of Allergy and Infectious Diseases (NIAID), working with other organizations and advocacy groups, led the development of the first clinical guidelines for the diagnosis and management of food allergy. A recent landmark clinical trial and other emerging data suggest that peanut allergy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
181
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 380 publications
(182 citation statements)
references
References 40 publications
(29 reference statements)
1
181
0
Order By: Relevance
“…The EAT study [ 33 ] also showed a reduced risk in the general population using the per protocol analysis, but not the intention to treat analysis. For peanut, clinical practice guidelines in the US have incorporated these findings and do recommend early peanut introduction in the first year of life for high- and standard-risk children [ 34 ]. However, despite some evidence for early introduction of egg, the US guidelines only made recommendations regarding peanut intake, and concluded that there was not enough evidence to suggest early introduction of egg.…”
Section: The Role Of Allergen Intake and Dietary Diversity In Prevmentioning
confidence: 99%
“…The EAT study [ 33 ] also showed a reduced risk in the general population using the per protocol analysis, but not the intention to treat analysis. For peanut, clinical practice guidelines in the US have incorporated these findings and do recommend early peanut introduction in the first year of life for high- and standard-risk children [ 34 ]. However, despite some evidence for early introduction of egg, the US guidelines only made recommendations regarding peanut intake, and concluded that there was not enough evidence to suggest early introduction of egg.…”
Section: The Role Of Allergen Intake and Dietary Diversity In Prevmentioning
confidence: 99%
“…However, the data are not strong enough and further studies are needed on the early introduction of egg to the infant diet in order to be considered for adoption into the regulatory guidelines as a means of primary prevention of egg allergy. In contrast, a recent addendum to the guidelines was created for the early introduction of peanut into infant diets to prevent peanut allergy [21]. The induction of oral tolerance to food allergens and its potential immunological mechanisms have been shown in animal models [22] but are not yet well established in humans.…”
Section: Discussionmentioning
confidence: 99%
“…9 The NIAID suggests specialist assessment and testing of infants for peanut allergy if they have severe eczema or definite egg allergy. 9 If safe to do so, peanuts should be introduced at age 4-6 months. Families of low-risk infants are advised to introduce peanut at ~6 months without prior testing.…”
Section: Commentmentioning
confidence: 99%
“…Food challenges can be offered in cases of parental anxiety. 9 Many paediatric and allergy societies around the world are similarly changing their recommendations based on these studies. It is, however, unlikely the World Health Organization will change its advice on exclusive breast feeding for 6 months given the serious threat of diarrheal illness in developing countries.…”
Section: Commentmentioning
confidence: 99%